MEDIA AND SUSTAINABLE DEVELOPMENT: AN ANALYSIS OF THE JOURNALISTIC COVERAGE OF THE UN ENVIRONMENTAL CONFERENCES (Desenvolvimento em Questão, 2020)
This article analyzes the implications of media coverage in relation to the concept of sustainable development. The investigation focused on presenting a case study on the coverage of the Environmental Conferences of the United Nations (UN) in 1972, 1992, 2002 and 2012 by Jornal de Santa Catarina (JSC). In this way, and through a morphological and content analysis, the work explores the treatment of the concept of sustainable development by the media, and how it could advance in understanding its dimensions and the need for permanent debate on such issues. The study pointed out that JSC superficially disseminated the concept of sustainable development, focusing especially on official information and the reproduction of news from national and international agencies.
Keywords: Media. Sustainable development. Santa Catarina Journal.